Exploring factors influencing academic staff attitude towards the implementation of total quality management (TQM) in higher education - Boulahlib, Loutfi; Abd. Manaf, Noor Hazilah; Ismail, Izhairi; Islam, Rafikul (Macrothink Institute, 2022)
This study aims to explore factors that influence attitudes towards implementing TQM among the academic staff in one of the Malaysian higher education institutions. A total of 270 questionnaires were distributed among academic staff at International Islamic University Malaysia (IIUM), and a total of 209 questionnaires were completed. The method that best fits with the objective of this research is exploratory factor analysis. The results showed that three factors influenced the attitude of the IIUM academic staff on the execution of TQM principles. The findings of this research may stimulate other institutions to apply TQM principles in education and how TQM can be implemented in higher education. Senior-level management should take the opportunity to work together with the academic staff to boost the learning process by providing them with a platform to voice their points of view and suggestions. This paper contributes to the TQM literature and provides an important insight into current knowledge. The findings allow for implications to be made for both top management and policymakers. Such studies are needed to increase awareness and examine TQM's applicability in higher education.